Statistical analysis of interdependence of ICT and economic development of selected European countries - Milan Stamenković; Marina Milanović; Dragana Rejman Petrović (Economic Themes, 2021)
The research focus on the analysis of interdependence of economic and ICT development results from the fact that, in recent decades, ICTs have become a dominant factor in generating socio-economic prosperity of countries. ICT expansion is a stimulus for economic growth, and vice versa. In order to empirically verify the observed interdependence, on the example of the selected 37 European countries, a two-stage statistical analysis was conducted, based on a combined application of cluster analysis and a oneway analysis of variance. Using specific data from 2017, the following was conducted: (a) formation of groups of countries by implementing cluster analysis based on the three structural components of the ICT Development Index; and (b) by applying the ANOVA method and using the values of GDP per capita, testing the validity of assumption regarding the existence of statistically significant differences, in terms of the achieved level of economic development between the formed groups of countries of different levels of ICT development. The obtained results suggest the extraction of three clusters of countries and the acceptance of the defined hypothesis. Serbia is classified within the cluster of medium ICT development level and is characterized by the value of GDP per capita that is significantly below the group average, which indicates the possibility and the need for improvement in the ICT field.
Keywords: C38; C12; O33; O47; O57; 330; statistical analysis; cluster analysis; ANOVA; ICT development; economic development; selected European countries